Arsenic and mercury concentrations in marine fish sourced from local fishermen and fish markets in mine-impacted communities in Ratatotok Sub-district, North Sulawesi, Indonesia. Issue 1 (15th July 2017) - Bentley, Keith; Soebandrio, Amin
Abstract: Mesel gold mine, Ratatotok Sub-district, North Sulawesi, Indonesia deposited about 4.5 million m 3 of detoxified tailings containing arsenic (As) and mercury (Hg) via a submarine pipeline into Buyat Bay. As and Hg analysis of 216 fish muscle tissue composites from subsistence fishermen, local markets and a reference market confirmed that mean As levels were comparable between locations (range 1.71 to 2.12 mg/kg wet weight (ww)) and < 10% of the Australia New Zealand standard. Mean Hg concentrations were highest for the artisanal fishermen group (0.23 mg/kg ww), similar between the local markets (0.11–0.14 mg/kg ww) and lower at the reference market (0.04 mg/kg ww). A 12-month fish availability study identified that the results were due to the different coral and deep ocean species assemblages. All mean values were < 50% of the FAO/WHO/Codex standard for Hg. The results confirmed that there was no contamination from the deposited submarine tailings. Graphical abstract: Highlights: Submarine placement of neutralised As and Hg tailing has not contaminated the fish. Local geochemical signatures are major contributors to As and Hg levels in fish. Consumer preference and market availability are major determinants of exposure. As and Hg in locally sourced diet fish are within international health standards.